Active-Passive Transition of an Fe-6 mass% Cr Surface in Acidic Sodium Sulfate Solutions Under a Laminar Flow Condition Evaluated by Ellipso-Microscopy and Channel Flow Electrode Method. Issue 5 (5th May 2021) - Fujimura, Akihiro; Kitagawa, Yuichi; Hasegawa, Yasuchika; Doi, Takashi; Fushimi, Koji
Abstract : Electrochemical ellipso-microscopy was combined with the channel flow triple electrode method to evaluate the active-passive transition behavior of Fe-6 mass% Cr in acidic sodium sulfate solutions under the control of mass-transport reaction. During potentiodynamic polarization of the Fe-6 mass% Cr specimen electrode (SE), the SE surface was monitored by ellipso-microscopy and generated Fe(II) and Cr(III) species from the SE were detected at two detector electrodes arranged downstream in parallel. Forced convection of the electrolyte solution affected the mass-transport process of Cr(III) species on the SE surface in the latter half of the active region. In addition, the electrolyte solution flow resulted in enhancement of the passivation process and Cr enrichment on the passive surface. The effects of the electrolyte solution flow on active-passive transition and improvement of the passive film resistance are discussed.